Odpowiedzi

2010-03-03T18:36:14+01:00
8a - 16 = 8(a - 2)
15b + 10 = 5(3b + 2)
16b - 12c = 4(4b - 3c)
12x + 36y = 12(x + 3y)
y - 3y = y(1 - 3)
15 a (do kwadratu) + 12b (do kwadratu) = 3(5a (kwadrat) + 4b (kwadrat))
24x (do kwadratu) - 16y = 4 (6x(kwadrat) - 4y)
12a (do kwadratu) - 8b = 4(3a[kwadrat] - 2b)
10n - 15m = 5(2n - 3m)

Mam nadzieję, że wszystko dobrze :)
1 5 1
2010-03-03T18:42:17+01:00
8a - 16= 8(a-2)
15b + 10=5(3b+2)
16b - 12c= 4(4b-3c)
12x + 36y=12(x+3y)
y - 3y= y(1-3)
15a |do kwadratu| + 12b |do kwadratu|= 3(5a|do kwadratu|+4b|do kwadratu|)
24x |do kwadratu| - 16y= 4(6x|do kwadratu|-4y|do kwadratu|)
12a |do kwadratu| - 8b= 4(3a|do kwadratu|-2b)
10n - 15 m=5(2n-3m)
1 5 1